2019
DOI: 10.1146/annurev-physiol-022516-034038
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of BK Channels by Beta and Gamma Subunits

Abstract: Ca2+- and voltage-gated K+ channels of large conductance (BK channels) are expressed in a diverse variety of both excitable and inexcitable cells, with functional properties presumably uniquely calibrated for the cells in which they are found. Although some diversity in BK channel function, localization, and regulation apparently arises from cell-specific alternative splice variants of the single pore–forming α subunit (KCa1.1, Kcnma1, Slo1) gene, two families of regulatory subunits, β and γ, define BK channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 167 publications
1
117
2
Order By: Relevance
“…TRPV4 activation increases epithelial permeability in the mouse mammary cell line HC11, and this is prevented by the BK channel blocker paxilline in the early phase [7]. We have not demonstrated the expression of BK channels in MDCK II cells, but they are known to be expressed in epithelial cells of the kidney and in C11-MDCK cells [22,34]. However, we observed no inhibition of GSK-induced TJ opening by paxilline.…”
Section: Discussionmentioning
confidence: 64%
“…TRPV4 activation increases epithelial permeability in the mouse mammary cell line HC11, and this is prevented by the BK channel blocker paxilline in the early phase [7]. We have not demonstrated the expression of BK channels in MDCK II cells, but they are known to be expressed in epithelial cells of the kidney and in C11-MDCK cells [22,34]. However, we observed no inhibition of GSK-induced TJ opening by paxilline.…”
Section: Discussionmentioning
confidence: 64%
“…Different tissues exhibit BK currents of varying voltage and Ca 2+ -dependent activation properties, underlying the complex roles for BK channels in regulating excitability. This cell and tissue-specific regulation is achieved via extensive alternative splicing of KCNMA1 transcripts, assembly with modulatory βand γ-regulatory subunits, and a variety of post-translational modifications (Kyle and Braun, 2014;Latorre et al, 2017;Gonzalez-Perez and Lingle, 2019). These mechanisms work together to tailor the voltage and Ca 2+ dependence of channel activation, as well as the kinetics of activation and deactivation gating, for the cell-specific function of BK channels in excitability or K + transport.…”
Section: Bk Channel Structurementioning
confidence: 99%
“…However, important physiological properties of BK channels including their voltage and Ca 2+ -sensitivity depend on one-to-one co-assembly of the four BKα subunits with four regulatory BKβ subunits, which can include one of four isoforms (BKβ1, β2, β3, β4). Considering that different BKβ isoforms can profoundly impact the BK channel phenotype, including cellular localization and electrophysiological properties such as voltage sensitivity, Ca 2+ sensitivity, and inactivation kinetics [40], an important next step would be to identify the precise BKβ isoform(s) that regulate mitoBK channels in renal tubular cells. Recently, a study utilizing BKβ1-KO mice reported that the BKβ1 isoform regulates mitoBK channels and is required for its mitochondrial localization and activation in cardiomyocytes [41].…”
Section: Nrk Cells Express Mitobk Channelsmentioning
confidence: 99%